2010
DOI: 10.1038/ejcn.2010.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with tocotrienol-rich fraction on immune response to tetanus toxoid immunization in normal healthy volunteers

Abstract: Background/Objectives: Vitamin E is an essential fat-soluble vitamin that has been shown to induce favorable effects on animal and human immune systems. The objective of this study was to assess the effects of tocotrienol-rich fraction (TRF) supplementation on immune response following tetanus toxoid (TT) vaccine challenge in healthy female volunteers. Subjects/Methods: In this double-blinded, placebo-controlled clinical trial, participants were randomly assigned to receive either placebo (control group) or 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 23 publications
(24 reference statements)
2
37
0
3
Order By: Relevance
“…For instance, γ-tocotrienol (γTE), a natural form of vitamin E rich in palm oil, has been reported to inhibit NF-κB activation in leukemia KBM-5 and other cancer cells (12) as well as macrophages (13, 14). Consistently, γTE supplementation inhibits proinflammatory cytokines in animals and human subjects (15, 16). Despite these interesting results, the molecular mechanism responsible for the anti-NF-κB effect has not been identified.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…For instance, γ-tocotrienol (γTE), a natural form of vitamin E rich in palm oil, has been reported to inhibit NF-κB activation in leukemia KBM-5 and other cancer cells (12) as well as macrophages (13, 14). Consistently, γTE supplementation inhibits proinflammatory cytokines in animals and human subjects (15, 16). Despite these interesting results, the molecular mechanism responsible for the anti-NF-κB effect has not been identified.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, A20 has been recognized as a tumor suppressor in lymphomas as A20 was inactivated in many lymphomas and reintroduction of A20 promoted apoptosis and growth arrest of cancer cells (4). Given that NF-κB target genes regulate cell proliferation, cytokines and survival, the induction of A20 and consequent inhibition of NF-κB by γTE likely contributes to its antiproliferative, proapoptotic, anti-inflammatory and immunomodulatory effects (12, 15, 16, 28). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some randomized trials have found a positive effect of vitamin E supplementation on vaccine responses. A randomized trial conducted among healthy Malaysian women aged 18 to 25 determined that vitamin E significantly increased anti-tetanus antibody titers following revaccination compared to placebo (31). A trial conducted in healthy U.S. elderly subjects also found that highdose vitamin E supplementation increased anti-tetanus titers and antibody responses to hepatitis B following vaccination, but there was no effect on diphtheria or pneumococcal polysaccharide vaccine responses (32).…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blinded, placebo-controlled clinical trial, healthy volunteers supplemented with 400mg of tocotrienol-rich fraction had increased production of anti-tetanus toxoid antibody, IL-4 and interferon-gamma induced by tetanus toxoid vaccine challenge but reduced IL-6, compared with placebos [144]. A topical formulation containing tocopherols and tocotrienols showed photoprotective effect in photosensitive subjects [145].…”
Section: Health Benefits In Human Clinical Studiesmentioning
confidence: 99%